2013
DOI: 10.1080/09670262.2013.796528
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature on the infradian growth rhythm inUlva lactuca(Chlorophyta)

Abstract: The vegetative growth of Ulva lactuca was studied to determine if the growth rate of the alga is driven by infradian rhythmicity. The influence of temperature on the infradian rhythm of growth was also investigated. Discs of Ulva were grown in controlled laboratory conditions at different combinations of temperature (5, 10, 15, 20°С) and irradiance (40 and 60 μmol photons m -2 s -1 ) under 12 : 12 h light : dark cycles. The growth rates exhibited a rhythmic pattern with one major peak every 2 or 3 days. Growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…Although some setups can be expensive and/or complicated (Nagel et al, 2012;Sirault et al, 2013), the use of small and cheap computer systems, such as offered by Raspberry Pi computers and cameras (Minervini et al, 2017), together with a relatively lowlevel informatics pipeline, allow for the creation of cheap and easy-to-use phenotyping platforms. In addition, we show in this study, in agreement with the literature (Titlyanov et al, 1996;Gordillo et al, 2001;Ale et al, 2011;Kalita and Titlyanov, 2013), that the disc-based proxy systems are appropriate for detecting differences in growth performance between Ulva strains, because a strong correlation was found between thallus growth and disc growth (Fig. 1C).…”
Section: Development Of a High Throughput Phenotyping Platformsupporting
confidence: 91%
“…Although some setups can be expensive and/or complicated (Nagel et al, 2012;Sirault et al, 2013), the use of small and cheap computer systems, such as offered by Raspberry Pi computers and cameras (Minervini et al, 2017), together with a relatively lowlevel informatics pipeline, allow for the creation of cheap and easy-to-use phenotyping platforms. In addition, we show in this study, in agreement with the literature (Titlyanov et al, 1996;Gordillo et al, 2001;Ale et al, 2011;Kalita and Titlyanov, 2013), that the disc-based proxy systems are appropriate for detecting differences in growth performance between Ulva strains, because a strong correlation was found between thallus growth and disc growth (Fig. 1C).…”
Section: Development Of a High Throughput Phenotyping Platformsupporting
confidence: 91%
“…Previous studies have found that the relative growth rates of Ulva spp. in cultivation generally increases with increasing irradiance (Geertz-Hansen and Sand-Jensen 1992; Riccardi and Solidoro 1996;Taylor et al 2001;Kalita and Tytlianov 2003;Kalita and Titlyanov 2013;Mhatre et al 2019). Light saturation for the growth of U. lactuca is suggested to occur at 55 μmol photons m −2 s −1 (Sand-Jensen 1988), and the growth of the seaweeds are not inhibited at irradiances up to 225 μmol photons m −2 s −1 (Fortes and Lüning 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Growth generally increases with increasing irradiance, temperature, nutrient, and pCO 2 levels (e.g. Duke et al 1986;Geertz-Hansen and Sand-Jensen 1992;Riccardi and Solidoro 1996;Taylor et al 2001;Kalita and Tytlianov 2003;Kalita and Titlyanov 2013;Olischläger et al 2013;Kumari et al 2014;Young and Gobler 2016;Gao et al 2017Gao et al , 2018aTremblay-Gratton et al 2018;Chen et al 2019;Mhatre et al 2019;Sebök et al 2019), although there are exceptions to this general pattern (e.g. Kerrison et al 2012;Liu and Zou 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, additional studies on plant tissue culture reported on seasonal impacts on plant tissue culture, grown under controlled conditions for 3 years, effects which could not be related directly to the starting biomass (Sharma, Hänsch, Mendel, & Schulze, ). Recent work on Ulva vegetative growth in the precisely controlled laboratory conditions showed that growth rates exhibited a rhythmic pattern with one major peak every 2 or 3 days, which authors related to large‐scale Rossby and Kelvin waves that produce oscillations in the geomagnetic fields (Kalita & Titlyanov, ). Our results indicate that for all flashing lights experiments, parallel control, cultivated under the constant light are needed.…”
Section: Resultsmentioning
confidence: 99%